2010
DOI: 10.1074/jbc.m109.090266
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Manganese Superoxide Dismutase by Nuclear Translocation and Activation of SIRT1 Promotes Cell Survival in Chronic Heart Failure

Abstract: Oxidative stress plays a pivotal role in chronic heart failure. SIRT1, an NAD ؉ -dependent histone/protein deacetylase, promotes cell survival under oxidative stress when it is expressed in the nucleus. However, adult cardiomyocytes predominantly express SIRT1 in the cytoplasm, and its function has not been elucidated. The purpose of this study was to investigate the functional role of SIRT1 in the heart and the potential use of SIRT1 in therapy for heart failure. We investigated the subcellular localization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
299
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 320 publications
(318 citation statements)
references
References 34 publications
16
299
2
1
Order By: Relevance
“…91) Tanno et al reported that manganese superoxide dismutase (Mn-SOD) was induced by 100 μM resveratrol via nuclear translocation and activation of SIRT1 in mouse myoblast C2C12 cells, and that the oral administration of resveratrol (0.4% in diet for 35 weeks) to TO-2 hamsters increased cardiomyocyte Mn-SOD levels, suppressed fibrosis, preserved cardiac function, and significantly improved survival. 92) These results are consistent with our finding that hepatic expression of SIRT1 and Mn-SOD genes was induced by 0.02% resveratrol in the diet for 4 weeks in wild-type mice, but not in PPARα knockout mice (manuscript in preparation). However, 50 μM resveratrol promoted fat mobilization in white adipocytes by repressing PPARγ in 3T3-L1 cells, 93) which is inconsistent with our finding that 5 μM resveratrol activates PPARα, β/δ, and γ in BAECs.…”
Section: Link To Sirt1 and Other Targetssupporting
confidence: 82%
“…91) Tanno et al reported that manganese superoxide dismutase (Mn-SOD) was induced by 100 μM resveratrol via nuclear translocation and activation of SIRT1 in mouse myoblast C2C12 cells, and that the oral administration of resveratrol (0.4% in diet for 35 weeks) to TO-2 hamsters increased cardiomyocyte Mn-SOD levels, suppressed fibrosis, preserved cardiac function, and significantly improved survival. 92) These results are consistent with our finding that hepatic expression of SIRT1 and Mn-SOD genes was induced by 0.02% resveratrol in the diet for 4 weeks in wild-type mice, but not in PPARα knockout mice (manuscript in preparation). However, 50 μM resveratrol promoted fat mobilization in white adipocytes by repressing PPARγ in 3T3-L1 cells, 93) which is inconsistent with our finding that 5 μM resveratrol activates PPARα, β/δ, and γ in BAECs.…”
Section: Link To Sirt1 and Other Targetssupporting
confidence: 82%
“…We have shown that SIRT1 is a nucleocytoplasmic shuttling protein (12,13). Furthermore, we found that resveratrol increases superoxide dismutase 2, inhibits cardiomyocyte death, and prolongs the life span in TO-2 cardiomyopathic hamsters (14). We also recently reported that resveratrol reduces oxidative stress and ameliorates the skeletal muscle pathology in mdx mice (15).…”
mentioning
confidence: 82%
“…1, F and G) in mdx mice. Previously, we showed that resveratrol represses skeletal muscle fibrosis in mdx mice (15) and cardiac fibrosis in cardiomyopathic TO2 hamsters (14). Down-regulation of ␣-smooth muscle actin expression in mdx hearts treated with resveratrol ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of Sirt1 activation to date have primarily focused on post-translational mechanisms of regulation. These mechanisms include changes in pyridine nucleotide levels or ratios that affect Sirt1 enzymatic activity, Sirt1 phosphorylation or other kinase-induced effects (35)(36)(37)(38)(39)(40), or Sirt1 subcellular localization (41)(42)(43)(44). Changes in pyridine nucleotide levels or ratios are perhaps the best studied mechanism for regulating Sirt1 function (45).…”
Section: Discussionmentioning
confidence: 99%